(untitled) (Altre Modernità, 2013)
The last part of Rubén Darío’s literary production was marked by a change in his poetics, that means he increased intimism, civil and political interests. In the chronicles written at the end of the 19th century, the change also concerns the author’s statement of European decadence and fall. In this period, in which Spain lost his colonies (1898), Darío focuses on the reasons why Spain (España contemporánea, 1901) and to some extent France (Peregrinaciones, 1901; Parisiana, 1908) got into an extensive cultural crisis. In this essay I get evidence of Dario’s political thought, pointing out the way in which he recognizes signs of decadence, and the arguments he uses, which imply an idealistic solution to problems.